Beneficial Effect of Paljeong-san Pharmacopuncture Treatment Combined with Peritoneal Injection on Glycerol-Induced Acute Renal Failure in Rabbits - Chi-Yeon Lim; Min-Ho Kim; Geum-San Lee; Hyung-Woo Kim; Bu-Yeo Kim; Yeo-Choong Yun; Su-In Cho (Korean Pharmacopuncture Institute, 2010)
Purpose: The present study was carried out to determine if Paljeong-san extract (PJS) treatment exerts beneficial effect against the glycerol-induced acute renal failure in rabbits. Material and Method: PJS was selected in the basis of invigorating kidney which can eliminate pathogens. Rabbits were treated with PJS pharmacopuncture on Shin-shu (BL23) point for 5 days right after the injection of 50% concentration of glycerol (5㎖/㎏ body weight). Results and Conclusions: Glycerol injection caused an increase in serum creatinine and BUN level and urine glucose secretion, which were accompanied by a reduction in GFR. PJS Pharmacopuncture treatment combined with peritoneal injection showed beneficial effect on glycerol-induced acute renal failure by inhibition of serum creatinine increase and GFR decrease.